Human Mutations in SLC2A9 (Glut9) Affect Transport Capacity for Urate - Ruiz, Anne; Gautschi, Ivan; Schild, Laurent; Bonny, Olivier (Frontiers in Physiology, 2018)
SLC2A9 or Glut9 is a voltage sensitive urate transporter, mainly expressed in the kidneys, the liver and the intestine. Human Glut9 loss-of-function mutations were identified in familial hypouricemia, and several single nucleotide polymorphisms (SNPs) were associated with lower serum urate, further indicating that Glut9 is a major determinant of serum uric acid level. To get insights in Glut9 transport characteristics, we systematically analyzed the function of known human Glut9 mutants using 14C-urate uptake assay and two-electrode voltage clamp (TEVC) in the X. laevis oocyte expression system. Surface expression was assessed by immunostaining and biotinylation. We found decreased urate transport by flux studies for most of the variants. No variant was permissive for glucose transport. We could further differentiate two behaviors among the mutants: those harboring poor overall and cell-surface expression leading to low activity and those fully expressed at the cell surface, but presenting decreased activity. We studied the latter by TEVC and observed, in depolarized conditions, decreased inward currents measured in presence of 400 µM urate, partially reversed in 1mM urate. In addition, we showed that C210F displays lower transport ability. By contrast, N333S showed decreased urate transport activity and urate affinity, suggesting that it may belong to the urate binding pocket. Systematic analysis of Glut9 mutants confirms Glut9 as putative target for the treatment of hyperuricemia and brings new insights in Glut9 structure – function.